Photographs of manipulable objects are named more quickly than the same objects depicted as line-drawings: Evidence that photographs engage embodiment more than line-drawings - Salmon, Joshua P.; Matheson, Heath E.; McMullen, Patricia A. (Frontiers in Psychology, 2014)
Previous research has shown that photographs of manipulable objects (i.e. those that can be grasped for use with one hand) are named more quickly than non-manipulable objects when they have been matched for object familiarity and age of acquisition. The current study tested the hypothesis that the amount of visual detail present in object depictions moderates these ‘manipulability’ effects on object naming. The same objects were presented as photographs and line-drawings during a speeded naming task. Forty-six participants named 222 objects depicted in both formats. A significant object depiction (photographs versus line drawing) by manipulability interaction confirmed our hypothesis that manipulable objects are identified more quickly when shown as photographs; whereas, non-manipulable objects are identified equally quickly when shown as photographs versus line-drawings. These results indicate that factors such as surface detail and texture moderate the role of “action” and/or “manipulability” effects during object identification tasks, and suggest that photographs of manipulable objects are associated with more embodied representations of those objects than when they are depicted as line-drawings.